Abu Bakar Al-Razi: Riwayat Hidup dan Konsep Lima Kekal Dalam Filsafatnya - N, Nurfadilah; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Abu Bakar Muhammad bin Zakariya al-Razi (865–925 AD), is known as one of the leading scientists, philosophers, and doctors in Islamic civilization. His rational and humanist thinking has a great influence in various fields, especially philosophy and medicine. One of al-Razi's most controversial philosophical contributions is the concept of al-Qudama al-Khamsa or his five eternals. In this view, al-Razi put forward five eternal entities: God, soul, matter, time, and space. Unlike the dominant theological views of his time, this concept emphasizes a rational approach that aims to explain the origins of the universe metaphysically. This study aims to examine the life history of al-Razi, the development of his thinking, and a critical analysis of his five eternal concepts. The method used is a literature study by tracing relevant primary and secondary sources. The results of the study show that al-Razi combines the philosophy of materialism with a rationalist view. Although his five eternal concepts have drawn much criticism from scholars and philosophers, the idea has made a significant contribution to the discourse on metaphysics and the philosophy of science in the Islamic and Western worlds.